(untitled) (KYAMC Journal, 2018)
Stevens-Johnson syndrome (SJS) is an immune complex mediated hypersensitivity complex that typically involves the skin and mucous membranes. While minor presentations may occur, significant involvement of oral, nasal, eye, vaginal, urethral, gastrointestinal, and lower respiratory mucous membranes may develop in the course of the illness. GI and respiratory involvement may progress to necrosis. Stevens-Johnson syndrome is a serious systemic disorder with the potential for severe morbidity and even death. The syndrome was first described in 1922, when the American pediatricians Albert Mason Stevens and Frank Chambliss Johnson reported the cases of 2 boys aged 7 and 8 years with "an extraordinary, generalized eruption with continued fever, inflamed buccal mucosa, and severe purulent conjunctivitis". Both cases had been misdiagnosed by primary care physicians as hemorrhagic measles. Erythema multiforme (EM), originally described by Von Hebra in 1866, was part of the differential diagnosis in both cases but was excluded because of the ’character of skin lesions, the lack of subjective symptoms, the prolonged high fever, and the terminal heavy crusting". Despite the presence of leucopenia in both cases, Stevens and Johnson in their initial report suspected an infectious disease of unknown etiology as the cause. In 1950, Thomas divided EM into 2 catagories: erythema multiforme minor (Von Hebra) and Erythema multiforme major (EMM). Since 1983, erythema multiforme major and Stevens-Johnson syndrome had been considered synonymous. In the 1990s, however, Bastuji and Roujeau each proposed that Erythema multiforme major and Stevens-Johnson syndrome are 2 distinct disorders. Several investigators propose that Stevens-Johnson syndrome and Toxic epidermal necrolysis (TEN) represent the same disease at different levels of severity. Although several classification schemes have been reported, the simplest breaks the disease down as follows: * Stevens-Johnson syndrome-A "minor form of TEN", with less than 10% body surface area (BSA) detachment. * Overlapping Stevens-Johnson syndrome/Toxic epidermal necrolysis (SJS/TEN)-Detachment of 10-30% BSA. * Toxic epidermal necrolysis-Detachment of more than 30%BSA. KYAMC Journal Vol. 8, No.-2, Jan 2018, Page 31-35